Treatment response evaluation in extraspinal musculoskeletal tuberculosis using molecular imaging (18F-fluorodeoxyglucose PET/computed tomography): a prospective observational study - Roshan Banjara; Dilip Kumar Sankhwar; Ashish Dutt Upadhyay; Jaiben George; Rakesh Kumar; Vivek Shankar; Venkatesan Sampath Kumar; Shah Alam Khan (Nuclear Medicine Communications, 2026)
Objective The aim of the study was to evaluate the role of 18 F-fluorodeoxyglucose (FDG) PET/computed tomography (CT) in monitoring treatment response and determining treatment end points in patients with extraspinal musculoskeletal tuberculosis (MSK-TB) receiving anti-tubercular therapy (ATT). Methods In this prospective observational study, 62 patients with extraspinal MSK-TB underwent baseline 18 F-FDG PET/CT before ATT, with follow-up scans at 6, 12, and 18 months. Total lesion glycolysis (TLG), maximum standardized uptake value (SUVmax), and lesion-to-liver standardized uptake value ratio (SUVR) were recorded. Clinical, laboratory, and MRI findings were used as reference standards for healing. Receiver operating characteristic analysis identified PET/CT parameters associated with ATT beyond 18 months. Results Fifty-one patients completed the final PET/CT follow-up. Significant reductions in TLG, SUVmax, and SUVR were observed during treatment (all P < 0.05). ROC analysis demonstrated that a ≤43% reduction in TLG, ≤46% reduction in SUVmax, and ≤26% reduction in SUVR between baseline and 6-month scans, and a ≤66% reduction in TLG, ≤36% reduction in SUVmax, and ≤30% reduction in SUVR between baseline and 12-month scans, were associated with the requirement for ATT beyond 18 months. The mean time to complete clinicoradiological healing was 19.23 ± 1.49 months, whereas the mean time to complete metabolic response on PET/CT was 18.54 ± 2.27 months, with no statistically significant difference ( P = 0.30). Conclusion 18 F-FDG PET/CT is a valuable tool for monitoring treatment response in extraspinal MSK-TB. Early changes in PET/CT parameters may predict treatment duration, and PET/CT findings closely correlate with disease healing, supporting its use in guiding individualized ATT duration.